FACE THE FEAR OF FALLING BEHIND IN THE DIGITAL AGE: RECOGNIZING AND OVERCOING FOMO - Mika Melliani; Ribka Wahyu Christian, Pilenia, Lela Oktaria, Daniel Np Simatupang, Enjelia, Yola Pradita; Yesyurun Munthe (CV. ADIBA AISHA AMIRA, 2024)
This article looks at the